2012
DOI: 10.2105/ajph.2012.300960
|View full text |Cite
|
Sign up to set email alerts
|

Leading Causes of Unintentional and Intentional Injury Mortality: United States, 2000–2009

Abstract: Objectives We have described national trends for the 5 leading external causes of injury mortality. Methods We used negative binomial regression and annual underlying cause-of-death data for US residents for 2000 through 2009. Results Mortality rates for unintentional poisoning, unintentional falls, and suicide increased by 128%, 71%, and 15%, respectively. The unintentional motor vehicle traffic crash mortality rate declined 25%. Suicide ranked first as a cause of injury mortality, followed by motor vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(139 citation statements)
references
References 36 publications
6
127
0
4
Order By: Relevance
“…These findings highlight the importance of addressing and preventing self-harm behavior in this age group. Although multiple studies have highlighted that rates of SII are increasing in both adolescents and adults, 4,5 this study represents the most current analysis in an adolescent population. Our finding that cut/pierce was the most common mechanism differs from an earlier study using data from the NTDB 6 and may indicate a shift in self-harm behavior in youth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings highlight the importance of addressing and preventing self-harm behavior in this age group. Although multiple studies have highlighted that rates of SII are increasing in both adolescents and adults, 4,5 this study represents the most current analysis in an adolescent population. Our finding that cut/pierce was the most common mechanism differs from an earlier study using data from the NTDB 6 and may indicate a shift in self-harm behavior in youth.…”
Section: Discussionmentioning
confidence: 99%
“…4 A recent analysis looking at all age groups found that mortality rates for suicide increased by 15% from 2000 to 2009, and that suicide has surpassed motor vehicle traffic crashes as the leading cause of injury mortality in the United States. 5 Although research has shown changing patterns in self-harm, the majority of studies examining ED visits for SII in adolescents have examined data from 2008 or earlier. 4,[6][7][8][9][10] For primary and secondary prevention, it is vital to have the most recent information possible to most accurately describe the current epidemiology of self-harm behavior in youth.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Suicide is the tenth leading cause of death in the US, and the number one cause of injury-related death-recently surpassing mortality due to motor vehicle traffic accidents. 1,2 Suicide accounts for the loss of nearly 37,000 American lives each year according to the Centers for Disease Control and Prevention, 1 and there is evidence that the suicide rate has not improved over time. 3,4 However, research suggests that suicide is potentially preventable.…”
Section: Introductionmentioning
confidence: 99%
“…Contiguous fractures are more common in children than in adults [6][7][8][9][10]. This is of great importance, because failure to detect concomitant injuries can lead to delayed instability and additional neurologic deterioration.…”
mentioning
confidence: 99%